Teachers' Perceptions Regarding the Urgency of Improving Critical Thinking in Early Children - Puspita, Yenda; Hanum, Farida; Rohman, Arif (International Journal of Membrane Science and Technology, 2023)
Teachers play the most important role in education apart from curriculum, infrastructure, methods, parents and the environment in improving critical thinking in early childhood as a quality generation towards golden Indonesia 2045. The purpose of this study is to describe teacher perceptions regarding the urgency of increasing critical thinking in early childhood as a quality generation towards golden Indonesia 2045. Teacher information regarding the urgency of increasing critical thinking in early childhood uses case studies with a qualitative approach. The informants consisted of 5 PAUD teachers in the city of Pekanbaru. The results of the study reveal that teachers feel that increased critical thinking is needed from early childhood towards a quality generation, especially in preparing for golden Indonesia 2045, teachers make efforts in the form of providing various learning strategies, teachers stimulate children's critical thinking with questions, teachers do not only try to improve cognitive, but also the attitudes and behavior of children make adab above knowledge.